ð˜–ð˜“ð˜ð˜Žð˜–ð˜•ð˜ ð˜Šð˜ð˜œð˜š ð˜ ð˜–ð˜›ð˜ð˜Œð˜™ð˜šð˜ (McGregor), UMA PRAGA POTENCIAL DO CHÃ - Flechtmann, Carlos H. W. (REVISTA DE AGRICULTURA, 2020)
ð˜–ð˜“ð˜ð˜Žð˜–ð˜•ð˜ ð˜Šð˜ð˜œð˜š ð˜ ð˜–ð˜›ð˜ð˜Œð˜™ð˜šð˜ (McGregor), UMA PRAGA POTENCIAL DO CHÃ